The Relationship Physical Activity And Smoking Behavior With The Incidence Of Hypertension In The Community In The Work Area Of The Rantang Health Center - Asima Wiranda Butar Butar; Hartono Hartono; Buenita S (CV. AFDIFAL MAJU BERKAH, 2026)
Hypertension is the leading cause of premature death worldwide. One of the global targets for non-communicable diseases is to reduce the incidence of hypertension by 33% in the period between 2010 and 2030. The purpose of this study is to determine the relationship between physical activity and. smoking and hypertension in the community in the working area of the Rantang Health Center. The population in this study is all hypertension patients at the Rantang Health Center as many as 1106 people with a sample of 92 respondents using the purposive sampling technique. This research method uses a cross sectional design with a chi square test resulting in a value (p = 0.05). The research instrument is in the form of a questionnaire sheet and a tool to check blood pressure, namely a sphygmomanometer. Based on the results of this study, it is shown that the variable of physical activity with the incidence of hypertension has a value (p=0.062). In the smoking behavior variable, the results of this study show that the number of smoking with the incidence of hypertension has a value (p = 0.003), the variable of the length of smoking with the incidence of hypertension has a value (p = 0.018), the variable of the type of smoking with the incidence of hypertension has a value (p = 0.003). The conclusion of this study is that there is no relationship between physical activity and the incidence of hypertension in the Rantang Puskesmas community, and The results of this study prove that smoking behavior, which is measured based on the number of cigarettes smoked, the length of smoking, and the type of cigarette is related to the incidence of hypertension in the Rantang Puskesmas community.